Soft Skills and Work Ethics of Language Program Graduates - Yohana Ika Harnita Sari; Erlin Estiana Yuanti; Endang Soelistiyowati (Politeknik Negeri Padang, 2020)
Graduates of vocational schools and polytechnics are expected to become skilled workers who are ready to work in various fields of work. Especially for graduates from language study programs, having the language skills and competence certificate is not enough to face the competition in the world of work. They also need to always perform soft skills and work ethics, to be able to get ready for working, to be able to understand colleagues better, and thus to adapt fast in any environment. Thus, there have been issues toward to what extent formal education specifically embeds soft skills and work ethics, what aspects of soft skills and work ethics that employees must possess, and what efforts have been given to develop them. This study aims at describing the efforts done by Language Study Programs, Sekolah Vokasi, Universitas Gadjah Mada (UGM)to adopt soft skills and work ethics and describing the performance of Language Study Programs, Sekolah Vokasi, UGM graduates in the aspects of soft skills (intrapersonal skill, interpersonal skill, and communication) and work ethics (commitment, integrity, professionalism, and hard work). The data were obtained by conducting observation and interview to the head of Language Study Programs and also administering a self-evaluation questionnaire, containing 47 items of soft skills and 44 work ethics items with five performance indicators (1: never – 5: always), that was distributed to 160 graduates from English, Korean, Japanese, and Chinese Language Study Programs of Sekolah Vokasi UGM. The finding of study suggests that efforts done are soft skills training session (in student orientation), etiquette lesson, support in organization participation, and internship program. The mean score of each indicator in the questionnaire is between 3.62 – 4.65 (out of 5). This score shows that the Language Study Programs graduates often and usually perform soft skills and work ethics that benefit them in the labor market.